Development of Virtual Reality as a Learning Media in Inactive Archives Management Course - Nurdiansyah, Aulia; Utami, Herwati Dwi; Wahyono, Effendi; Hermawati, Yanti (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
This research is motivated by the lack of development of learning media in the student learning process. Learning media that is already running is monotonous and tends to be boring. The purpose of this research is to develop learning media in the form of virtual reality technology. The benefits of this research are that it is hoped that students will gain real experience with the Manajemen Arsip Inaktif Course which is a Practical Course. The method used in this research is Research and Development, with stages from potentials and problems to producing the final product. The results of this study are learning media in the form of virtual reality. Applications generated using the Game Engine Unity can be run on a device in the form of an Android-based smartphone and can be integrated with a VR Headset. At the evaluation stage, it was found that the parameter evaluation results were obtained from material experts (90.69%), learning design experts (84.74%), and media experts (94.64%). From the results of the study, it was concluded that virtual reality-based learning media has very good feasibility to be applied to Manajemen Arsip Inaktif course at Universitas Terbuka.